The Influence of Translation Techniques on the Accuracy and Acceptability of Translated Utterances that Flout the Maxim of Quality - Ria Aresta (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Translating the implied meanings in utterances is one of the trickiest situations translators may confront. One example is in translating utterances that flout the maxim of quality. When a speaker flouts the maxim of quality, they are implying further information that is not represented in the utterance. Translators use various translation techniques in order to convey the meaning of the original text in the most appropriate and acceptable form in the target text. This study investigates how translation techniques may affect the quality of a translation. The approach implemented in this study is pragmatics in translation. This study belongs to the field of descriptive qualitative research with an embedded case study. For data, we look at all the utterances which may be said to be flouting the maxim of quality in the source text and its translation. Content analysis and focus group discussion were applied as the methods to collect and analyze the data. A focus group discussion was used to assess translation quality. The majority of the data was classified as accurate and acceptable, while the rest was considered less accurate and inaccurate due to the application of the translation technique amplification (addition), discursive creation and literal translation. Some data was also found to be less acceptable due to literal translation and pure borrowing.